Determinan Audit Judgment: Studi Pada Kantor Akuntan Publik di Jakarta Selatan - Nurul Hasanah; Iin Rosini (Akuntabilitas, 2016)
This research was compiled to find out how the influence of the pressure of obedience, the complexity of the task and the experience of the auditors audit against the judgment on the public accountant in South Jakarta. Research methodology used use descriptive method quantitative and using primary data secondary. Selection of a sample probability samplingwith the purposive approach to sampling and samples used totaled 9 HOOD with a total of 57 respondents total auditor. The result of multiple linear Regression obtained 9,539 Y = + 0, 563X1 + 0, 4111X2 + 0, 720X3. The t-test based procured and X 1 (0,022 < 0.05), x 2 (0,064 > 0.05), X 3 (0.003 < 0.05) so the inferred stress obedience and partially influential auditor experience significantly to audit judgement and the complexity of the tasks partially do not affect significantly to audit judgement.